Creating possibility spaces for the development of circular bioeconomy initiatives - Per-Anders Langendahl; Cecilia Mark-Herbert; Matthew Cook (Journal of Integrative Environmental Sciences, 2022)
ABSTRACTTo help move society towards more sustainable states, policies have been developed in various countries to create a circular bioeconomy (CBE) in biobased sectors such as forestry and agriculture. In operationalizing CBE, initiatives must be created in which feedback loops between life-cycle stages are established to enable a “stock” of resources to be recirculated in the economy. By creating such feedback loops, CBE aims to decouple economic growth from natural resource depletion and degradation. However, few CBE initiatives have been developed. This implementation gap has partly arisen because policies to promote CBE are somewhat theoretical and do not seem to be informed by the practical realities of implementing CBE initiatives on the ground. While CBE policies do not and should not set out detailed implementation plans to address these issues, they do need to better account for how favourable circumstances and contexts can be created for the development of CBE initiatives. In response, this paper critically examines how possibility spaces can be created for the development of CBE initiatives. Assemblage thinking is used in longitudinal case study research focused on a major CBE initiative situated in the south of Sweden: Foodhills. Assemblage thinking is both an approach and method widely used in geography to study how spaces for action such as the construction of CBE initiatives are created. As such, the paper identifies and unpacks multiple issues arising in the development of CBE initiatives on the ground including geographical relations, actor networks and power.